Analisis Faktor yang Berhubungan dengan Perilaku Gaya Hidup Sehat pada Remaja Kecanduan Game Online - Asiyami Ranistiya Widyaningrum; Syamsulhuda Budi Musthofa; Farid Agushybana (Journal of Telenursing (JOTING), 2023)
This study analyzes factors related to healthy lifestyle behavior in teenagers addicted to online games. The method used is a quantitative approach with a cross-sectional survey design. The research results show that the dominant factors related to healthy lifestyle behavior in adolescents are gender, perceived barriers, perceived severity, friend support, teacher support, self-efficacy, promotion, and education. The variable with the largest Odds Ratio is the promotion variable with OR= 2.477 (95% CI: 1.392-4.405). In conclusion, promotion and education variables are the most dominant factors related to healthy lifestyle behavior in adolescents. Keywords: Factors, Online Game Addiction, Healthy Lifestyle Behavior, Teenagers